Multi‐jet fusion for additive manufacturing of radiotherapy immobilization devices: Effects of color, thickness, and orientation on surface dose and tensile strength. Issue 4 (25th February 2022) - Asfia, Amirhossein; Deepak, Basaula; Novak, James Ivan; Rolfe, Bernard; Kron, Tomas
Abstract: Immobilization devices are used to obtain reproducible patient setup during radiotherapy treatment, improving accuracy, and reducing damage to surrounding healthy tissue. Additive manufacturing is emerging as a viable method for manufacturing and personalizing such devices. The goal of this study was to investigate the dosimetric and mechanical properties of a recent additive technology called multi‐jet fusion (MJF) for radiotherapy applications, including the ability for this process to produce full color parts. Skin dose testing included 50 samples with dimensions 100 mm × 100 mm with five different thicknesses (1 mm, 2 mm, 3 mm, 4 mm, and 5 mm) and grouped into colored (cyan, magenta, yellow, and black (CMYK) additives) and non‐colored (white) samples. Results using a 6 MV beam found that surface dose readings were predominantly independent of the colored additives. However, for an 18 MV beam, the additives affected the surface dose, with black recording significantly lower surface dose readings compare to other colors. The accompanying tensile testing of 175 samples designed to ASTM D638 type I standards found that the black agent resulted in the lowest ultimate tensile strength (UTS) for each thickness of 1–5 mm. It was also found that the print orientation had influence on the skin dose and mechanical properties of the samples. When all data were combined and analyzed using a multiple‐criteria decision‐making technique, magenta was found to offer the best balance between high UTS and low surface dose across different thicknesses and orientations, making it an optimal choice for immobilization devices. This is the first study to consider the use of color MJF for radiotherapy immobilization devices, and suggests that color additives can affect both dosimetry and mechanical performance. This is important as industrial additive technologies like MJF become increasingly adopted in the health and medical sectors.